Circulating Mucosal-Associated Invariant T Cells in a Large Cohort of Healthy Chinese Individuals From Newborn to Elderly - Chen, Pengcheng; Deng, Wenhai; Li, Dandan; Zeng, Tai; Huang, Ling; Wang, Qun; Wang, Jinli; Zhang, Weiguang; Yu, Xiaoxiao; Duan, Deming; Wang, Jinle; Xia, Hong; et al. (Frontiers in Immunology, 2019)
Mucosal-associated invariant T (MAIT) cells, which are enriched in human blood and express a semi-invariant TCR chain, play important roles in conditions such as infectious diseases and cancer. The influence of age on levels and functional characteristics of circulating MAIT cells have not been fully addressed. Here we have collected blood samples from a large cohort of healthy Chinese individuals from newborn (cord blood) to the elderly and assessed the levels of circulating MAIT cells as well as their phenotype, activation and apoptosis status and cytokine expression profiles after in vitro stimulation. We found that the frequencies of circulating MAIT cells gradually increased in blood from newborns as they progressed into adulthood (20-40 years old) but then decreased during further progression towards old age (>60 years old). The lowered numbers of circulating MAIT cells in the elderly was correlated with a gradual increase of apoptosis. A majority of circulating MAIT cells expressed the chemokine receptors CCR5 and CCR6, and most also expressed CD8 and CD45RO. Few expressed CD69 in cord blood, but the frequency increased with age. Upon in vitro activation with PMA plus ionomycin or IL12 plus IL18, fewer MAIT cells isolated from the young adult group expressed IFN-γ, IL17A and Granzyme B then cells from other age groups while the proportion of cells that expressed TNF-α was similar. Taken together, our data provide information for guiding the assessment of normal levels and phenotypes of MAIT cells at different ages in healthy individuals and patients.